STRATEGY TO PREVENT JAMAAH ISLAMIYAH TERROR IDEOLOGY BY THE ACEH REGIONAL TASK FORCE IN ACEH TAMIANG - Khairinnas (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This study aims to analyze the strategy of preventing the terror ideology of Jamaah Islamiyah (JI) by the Aceh Regional Task Force Densus 88 Anti-Terror Police in Aceh Tamiang Regency. The analysis is grounded in Karl Mannheim’s theory of ideology and utopia, alongside the police function theory in counterterrorism. A qualitative case study approach was adopted, involving in-depth interviews, participatory observations, and document analysis. The findings reveal that JI’s ideology in Aceh Tamiang is deeply rooted through social networks, conservative religious education, and kinship-based recruitment. The Task Force has implemented three main strategies: early detection and preemptive actions, preventive approaches, and repressive enforcement. However, the application of the pentahelix model intended to involve government, academia, media, business sector, and civil society remains suboptimal. Limited personnel, insufficient budget, and lack of specialized training pose significant challenges to the effectiveness of counter-radicalization programs. This study concludes that the effectiveness of preventing the terror ideology of Jama Islamiyah in Aceh Tamiang is highly dependent on strengthening cross-sector synergy and increasing the institutional capacity of the Aceh Task Force Densus 88 AT Polri.